2015
DOI: 10.3390/w8010001
|View full text |Cite
|
Sign up to set email alerts
|

Wetland Accretion Rates Along Coastal Louisiana: Spatial and Temporal Variability in Light of Hurricane Isaac’s Impacts

Abstract: Abstract:The wetlands of the southern Louisiana coast are disappearing due to a host of environmental stressors. Thus, it is imperative to analyze the spatial and temporal variability of wetland vertical accretion rates. A key question in accretion concerns the role of landfalling hurricanes as a land-building agent, due to their propensity to deposit significant volumes of inorganic sediments. Since 1996, thousands of accretion measurements have been made at 390 sites across coastal Louisiana as a result of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 32 publications
2
17
0
Order By: Relevance
“…Each plot was then sampled bi-annually for 2 years and less frequently in subsequent years (Folse et al 2014). See other literature (Cahoon and Turner 1989;Folse et al 2014;Bianchette et al 2015) for more details on the feldspar methodology including limitations and benefits as well as details about downloading accretion data from the Coastal Information Management System (CIMS).…”
Section: Accretion Estimatesmentioning
confidence: 99%
See 1 more Smart Citation
“…Each plot was then sampled bi-annually for 2 years and less frequently in subsequent years (Folse et al 2014). See other literature (Cahoon and Turner 1989;Folse et al 2014;Bianchette et al 2015) for more details on the feldspar methodology including limitations and benefits as well as details about downloading accretion data from the Coastal Information Management System (CIMS).…”
Section: Accretion Estimatesmentioning
confidence: 99%
“…Accretion is commonly measured via marker horizons, such as feldspar, and particle-reactive radiotracers, such as 7 Be, 137 Cs, and 210 Pb (Callaway et al 1996;Taylor et al 2013). These methodologies are complementary: feldspar marker horizons measure accretion on a short time scale, months to years, (Cahoon and Turner 1989;Bianchette et al 2015) whereas 137 Cs and 210 Pb measure accretionary processes over decadal timescales to a century or more (Delaune et al 1978). Primary production processes dominate over decomposition processes in the surface layers (top~10 cm) of the wetland soil column, which significantly influences the accumulation of organic matter and carbon content of marsh soils (Hatton et al 1983;Nyman et al 2006;Turner et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Multiple hurricanes, including Katrina (2005), Rita (2005), Ike (2008), Gustav (2008), and Isaac (2012) have affected the Mississippi River delta region within the last few decades alone [8,36,37]. Several studies have shown that hurricanes are important sediment sources to coastal environments and play a crucial role in the erosion, transport, and deposition of coastal sediments in Louisiana [36][37][38][39][40]. Hurricanes can cause storm surge in excess of 6 m in the northern Gulf of Mexico [10,23], which is more than high enough to overtop any of the barrier beaches on the Caminada-Moreau headland [23] and can rapidly cause both ephemeral and permanent alterations to coastal features.…”
Section: Study Regionmentioning
confidence: 99%
“…The physical processes can strongly affect sediment transport and deposition, which would result in spatial and temporal variability of vertical accretion rates in coastal wetlands. The study by Bianchette and others [14] utilized an existing database (CRMS-Coastal Reference Monitoring System) with thousands of wetland accretion measurements at 390 sites across coastal Louisiana to analyze the spatial and temporal variability of their elevation changes. Specifically, the study mapped accretion rates in the region during time periods before, around, and after the landfall of Hurricane Isaac of 2012.…”
Section: Sediment Deposition and Land Creationmentioning
confidence: 99%